2022
DOI: 10.3390/molecules27072055
|View full text |Cite
|
Sign up to set email alerts
|

Tea Seed Kaempferol Triglycoside Attenuates LPS-Induced Systemic Inflammation and Ameliorates Cognitive Impairments in a Mouse Model

Abstract: (1) Background: The current research intended to obtain functional compounds from agricultural by-products. A functional tea seed flavonoid, kaempferol-3-O-[2-O-β-d-xylopyranosyl-6-O-α-L-rhanmopyranosyl]-β-d-glucopyranoside (KXRG), was isolated from tea seed dregs. We further determined its chemical structure and evaluated the protective effects of KXRG against local and systemic inflammation in vivo; (2) Methods: First, cytotoxicity and proinflammatory cytokine release were examined in a cell-culture system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Also, RAW264.7 cells were incubated with nontoxic concentrations of KXRG for 2 h then LPS was added for 24 h. KXRG had a protective effect against LPS in RAW264.7 cells at a nontoxic dose by suppressing IL‐6. Also, in vivo study revealed KXRG improved cognition following LPS via attenuation of serum pro‐inflammatory cytokines, decreasing COX‐2 expression in the cortex and hippocampus, and inhibition of IL‐6, TNF‐α, and IL‐1β 41 . In another study, BV2 cells were pretreated with kaempferol (10, 30, 50, and 100 μM) for 1 h then LPS was added at the dose of 1 μg/ml for 24 h. Kaempferol significantly reduced the generation of NO, PGE2, TNF‐α, IL‐1β, and ROS dose‐dependently.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, RAW264.7 cells were incubated with nontoxic concentrations of KXRG for 2 h then LPS was added for 24 h. KXRG had a protective effect against LPS in RAW264.7 cells at a nontoxic dose by suppressing IL‐6. Also, in vivo study revealed KXRG improved cognition following LPS via attenuation of serum pro‐inflammatory cytokines, decreasing COX‐2 expression in the cortex and hippocampus, and inhibition of IL‐6, TNF‐α, and IL‐1β 41 . In another study, BV2 cells were pretreated with kaempferol (10, 30, 50, and 100 μM) for 1 h then LPS was added at the dose of 1 μg/ml for 24 h. Kaempferol significantly reduced the generation of NO, PGE2, TNF‐α, IL‐1β, and ROS dose‐dependently.…”
Section: Resultsmentioning
confidence: 97%
“…Also, in vivo study revealed KXRG improved cognition following LPS via attenuation of serum pro-inflammatory cytokines, decreasing COX-2 expression in the cortex and hippocampus, and inhibition of IL-6, TNF-α, and IL-1β. 41 In another study, BV2 cells were pretreated with kaempferol (10, 30, 50, and 100 μM) for 1 h then LPS was added at the dose of 1 μg/ml for 24 h. Kaempferol significantly…”
Section: Bacterial Toxinsmentioning
confidence: 99%
“…In context of sepsis model, kaempferol plays an important role in anti-inflammatory response. Kaempferol would improve liver injury in sepsis rat model by selective COX-2 inhibition [ 23 ]. Bian et al reported that kaempferol reduced excessive production of TNF-α, IL-1β, IL-6, ICAM-1, and VCAM-1 in LPS group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of inflammatory response, kaempferol could regulate the inflammatory response by controlling CD3+ T cell infiltration [ 20 ], CD4+FoxP3+ regulatory T cells [ 21 ], and Ag-specific T cells in both in vivo and in vitro experiments [ 20–22 ]. Moreover, kaempferol inhibited inflammatory markers such as Cyclooxygenase-2 (COX-2), tumor necrosis factor-α (TNF-α), Interleukin-1β (IL-1β), Interleukin-6 (IL-6), Intercellular cell adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…More and more studies have proved that quercetin exerts renal protective effects through a variety of ways, including inhibiting ferroptosis, preventing the aging of the kidney cells, alleviating renal fibrosis and apoptosis, and repressing oxidative stress and inflammation [ 36 , 37 ]. As a natural anti-inflammatory compound, kaempferol has been reported to exert curative effects on kidney inflammatory damage [ 38 ]. Recently, numerous studies have shown that kaempferol has salutary effects for anti-inflammatory, antioxidant, analgesic, and anticancer properties [ 39 ].…”
Section: Discussionmentioning
confidence: 99%